Unique Cytokine Signature in the Plasma of Patients with Fibromyalgia - Jamie Sturgill; Elizabeth McGee; Victoria Menzies (Journal of Immunology Research)
Fibromyalgia (FMS) is a chronic pain syndrome with a complex but poorly understood pathogenesis affecting approximately 10 million adults in the United States. The lack of a clear etiology of FMS has limited the effective diagnosis and treatment of this debilitating condition. The objective of this secondary data analysis was to examine plasma cytokine levels in women with FMS using the Bio-Plex Human Cytokine 17-plex Assay. Post hoc analysis of plasma cytokine levels was performed to evaluate patterns that were not specified a priori. Upon examination, patients with FMS exhibited a marked reduction in TH2 cytokines such as IL-4, IL-5, and IL-13. The finding of this pattern of altered cytokine milieu not only supports the role of inflammation in FMS but also may lead to more definitive diagnostic tools for clinicians treating FMS. The TH2 suppression provides strong evidence of immune dysregulation in patients with FMS.